Pengaruh Terapi Murottal Al-Quran terhadap Kualitas Tidur pada Pasien Congestive Heart Failure (CHF) - Eka Meli Agustin; Indah Sri Wahyuningsih; Retno Setyawati (Journal of Medical Practice and Research, 2025)
Patients with Congestive Heart Failure (CHF) frequently experience sleep quality disturbances due to dyspnea, anxiety, and physical discomfort, which may worsen their physical and psychological conditions. One non-pharmacological intervention that may improve sleep quality is Al-Qur’an murottal therapy, as it provides relaxation and calming effects. This study aimed to determine the effect of Al-Qur’an murottal therapy on sleep quality in CHF patients. This study employed a quasi-experimental design with a one group pretest-posttest approach. A total of 17 respondents were selected using purposive sampling based on inclusion criteria. Sleep quality was measured using the Richards-Campbell Sleep Questionnaire (RCSQ). Al-Qur’an murottal therapy was administered for 15–20 minutes once daily for two consecutive days. Data were analyzed using the Wilcoxon test. The results showed that before the intervention, most respondents had poor sleep quality (58.8%). After the intervention, the majority of respondents experienced improved sleep quality, with 88.2% categorized as having good sleep quality. The Wilcoxon test revealed a p-value < 0.05, indicating a statistically significant difference in sleep quality before and after the intervention.